العوامل المؤثرة في الأداء الاكاديمي للطالب في كلية الاقتصاد بجامعة تشرين - حيدر, عز الدين (Latakia University Journal - Economic and Legal Sciences Series, 2019)
Our research aims to investigate factors, affecting student academic performance in faculty of economics in Tishreen University, buy a random sample from students of the last year in this faculty. We used multivariate analysis and discriminate analysis to determine factors that significantly affect student academic performance and to improve the academic performance of students in this faculty. The results of our study indicate the following: The conformity of Student’ tendency with his desires, and economic stimulations have the most effect on student academic performance in faculty of economics in Tishreen University, and their effect is significant on a significant level α=0.05 There are no significant differences in student academic performance between departments of faculty of economics in Tishreen University on a significant level α=0.05 . Student satisfaction on his Specialist, and economic stimulations have a significant classification effect on student academic performance in faculty of economics in Tishreen University on a significant level α=0.05 There are significant Classification model to classify students of this faculty by their academic performance on a significant level α=0.05. Classification of sample observation by discriminate model was significant on a significant level α=0.05. هدف البحث إلى تقصي العوامل المؤثرة في الأداء الأكاديمي لطلبة كلية الاقتصاد بجامعة تشرين من خلال عينة عشوائية تضم طلبة السنة الرابعة في هذه الكلية. استخدم في هذا البحث كل من التحليل متعدد المتغيرات والتحليل التمييزي الخطي لمعرفة العوامل المؤثرة في الاداء الأكاديمي للطالب والمساهمة في تحسين اداء طلبة هذه الكلية. توصل البحث إلى النتائج التالية: 1- توافق التخصص مع ميول الطالب والمحفزات الاقتصادية لهما أعلى تأثر في الأداء الأكاديمي لطلبة كلية الاقتصاد بجامعة تشرين وتأثير هذين العاملين معنوي عند مستوى دلالة α=0.05 . 2- لا يوجد فرق ذو دلالة احصائية في الأداء الأكاديمي للطالب بين اقسام كلية الاقتصاد عند مستوى دلالة α=0.05 3- لكل من توافق التخصص مع ميول الطالب و المحفزات الاقتصادية أثر تصنيفي ذو دلالة احصائية في الأداء الاكاديمي لطلبة كلية الاقتصاد بجامعة تشرين عند مستوى دلالة α=0.05 . 4- يوجد نموذج لتصنيف طلبة كلية الاقتصاد بجامعة تشرين وفق معيار الأداء الأكاديمي للطالب وهو معنوي عند مستوى دلالة α=0.05. 5- تصنيف مفردات العينة وفق النموذج المقترح ذو دلالة احصائية عند مستوى معنوية α=0.05 حسب اختبار Q statistic.